2011
DOI: 10.11606/issn.2316-9036.v0i89p174-189
|View full text |Cite
|
Sign up to set email alerts
|

As fundações estaduais de amparo à pesquisa e o desenvolvimento da ciência, tecnologia e inovação no Brasil

Abstract: Este artigo apresenta o contexto científico nacional e internacional com foco na trajetória pavimentada ao longo dos anos no Brasil e na perspectiva que pode ser inferida a partir do histórico traçado. Demonstra-se que o país não pode mais depender apenas do sucesso alcançado nos últimos anos no indicador de produção científica indexada. Precisa, urgentemente e de forma ágil, mudar de patamar e se transformar numa potência científica e tecnológica mundial. Os casos de sucesso mais recentes são apresentados par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 1 publication
0
8
0
10
Order By: Relevance
“…The number of studies' oscillations over the last decades possibly reflects a regional asymmetry of the Brazilian scientific production with Southern and Southeastern regions hosting several research centers (undergraduate and graduate courses; Santos & Azevedo, 2009) that fueled the national research. Despite recent state governmental efforts to minimize this asymmetry (Borges, 2010), such as the creation of the state research foundations (FAPEG in the case of Goiás State), this situation is still observed and encompasses different scientific knowledge areas (Dias et al, 2016). An example of this situation is the research project conducted in the Serra da Mesa reservoir, Tocantins River basin, and financed by FURNAS Centrais Elétricas [FURNAS Central Electric] (FURNAS).…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies' oscillations over the last decades possibly reflects a regional asymmetry of the Brazilian scientific production with Southern and Southeastern regions hosting several research centers (undergraduate and graduate courses; Santos & Azevedo, 2009) that fueled the national research. Despite recent state governmental efforts to minimize this asymmetry (Borges, 2010), such as the creation of the state research foundations (FAPEG in the case of Goiás State), this situation is still observed and encompasses different scientific knowledge areas (Dias et al, 2016). An example of this situation is the research project conducted in the Serra da Mesa reservoir, Tocantins River basin, and financed by FURNAS Centrais Elétricas [FURNAS Central Electric] (FURNAS).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at the beginning of the 2000s, the Biota/FAPESP program supported taxonomy research studies, including many crustacean groups). Borges (2011) (São Paulo, 2014). A similar number of publications were recorded for the states of Minas Gerais and Paraná, which each host a significant number of researchers specializing in microcrustaceans and limnology.…”
Section: Discussionmentioning
confidence: 99%
“…A produção de conhecimento e do fomento à ciência, de acordo com Borges (2011), é muito recente e tem pouco mais de meio século.…”
Section: Produção E Comunicação Do Conhecimentounclassified